Tactical Urbanism - Lydon, Mike (Springer, 2015)
Short-term, community-based projects—from pop-up parks to open streets initiatives—have become a powerful and adaptable new tool of urban activists, planners, and policy-makers seeking to drive lasting improvements in their cities and beyond. These quick, often low-cost, and creative projects are the essence of the Tactical Urbanism movement. Whether creating vibrant plazas seemingly overnight or re-imagining parking spaces as neighborhood gathering places, they offer a way to gain public and government support for investing in permanent projects, inspiring residents and civic leaders to experience and shape urban spaces in a new way.